Pemaknaan Warna Merah Dengan Konotasi Barthes pada Iklan Mobil Ferrari - Dewi Nuryanti (ESENSI LINGUA, 2022)
The research was aimed to explain the meaning of a sign marked by the red color at Ferrari’s Advertisement. In addition, the research was done in order to describe about the connotation meaning perceived by the its audiences. To analyze the data, the writer used the theory of connotation by Barthes. The result of the analysis showed that connotation could emerge differently in society for the same sign. It was related to society’s shared knowledge about one thing or about their culture. Connotation given by society toward Ferrari or its logo and/or its color was seen to have a close related to the Formula 1 racing arena, or to Italian fancy red car. Furthermore, the society’s perspektive toward this advertisement found that people interpreted the owner of the product as the jetset ones since the products was a very luxurious products which was not owned by the middle-low class.